Branding Community Paguyuban Perajin Wayang Purwa Dusun Gendeng Bangunjiwo Yogyakarta sebagai Penguatan Kawasan Mandiri Budaya - Susanto, Moh. Rusnoto; Siti Mariah; Ambar Lukitaningsih; Sugiyarto Surono (Jurnal Senirupa Warna, 2025)
Gendeng Hamlet in Bangunjiwo Bantul is a hamlet where shadow puppet craftsmen grow as one of the oldest craft centers in Bangunjiwo. The craftsmen continue to survive and consistently maintain the tradition of leather puppet inlay and try to restore its golden age. Thus, the purpose of writing this article is to disseminate how the puppet craftsmen of Gendeng Hamlet continue to maintain their existence as the Gendeng Leather Puppet Craft Center through improving product quality and rebranding the Mandiri Budaya area. The participatory-based descriptive qualitative method is in line with the determination of the PM UPUD community assistance program, which is collaborative and participatory. The stages of implementation are as follows: stages or steps in implementing the solutions offered to overcome the problems of target partners. Describe the method of implementing the stages of community service every year, at least containing the following: Socialization, Training, Application of technology, Mentoring and evaluation, and Program Sustainability. The program outputs is increased capacity of superior products, up-skilling of creative human resources, transfer of planning. The flagship product of the Gendeng Tatah Sungging Craft Center is shadow puppets. More specifically, Yogyakarta-style shadow puppets. The results achieved include: (1) Puppet craftsmen in Gendeng hamlet are able to increase the capacity of creative human resources and high-quality production capacity. (2) Strengthening product branding and rebranding the Independent Culture area through the Gendeng shadow puppet crafters community to be able to penetrate foreign markets.